Fishing line suture: cost-saving alternative for atraumatic intracutaneous skin closure - randomized clinical trial in Rwanda - Freudenberg, Sebastian; Nyonde, Martin; Mkony, Charles; Bay, Fatma; Wilhelm, Torsten; Post, Stefan (World journal of surgery, 2004)
Experience with the use of nylon fishing line for surgical sutures has been reported from several African countries. A recent publication suggested that fishing line and an injection needle may provide an atraumatic suture that is especially suitable for intracutaneous skin closures. This article provides further empirical support for such alternative technology. We describe a randomized, blinded clinical trial conducted in Butare (Rwanda) with 220 cutaneous wounds closed by intracutaneous sutures, with either the homemade suture or a commercial nylon thread (Ethilon). We compared the clinical outcomes as well as the costs of those two materials. There are no significant differences between the two sutures in terms of clinical findings or in the reported ease of use by the surgeons. The cost of a homemade atraumatic suture is US $0.07, which is less than one-thirtieth the cost of the commercial thread. The advantage of the commercial thread is the assurance of quality. We consider whether this quality assurance justifies the large price difference, and if the homemade suture should be recommended to surgeons in countries where the costs of surgical material often remain an obstacle for life-saving operations.
Gesehen am 31.05.2022